Engineering modular integrated construction for high-rise building: a case study in Hong Kong. Issue 6 (15th April 2019) - Shan, Sidi; Looi, Daniel; Cai, Yancheng; Ma, Peng; Chen, Man-Tai; Su, Ray; Young, Ben; Pan, Wei
Abstract : Modular construction has been adopted as a new form of construction to enhance quality and productivity. However, most of the success stories of adopting modular systems are limited to low-rise buildings. This paper explores the feasibility of engineering modular integrated construction systems for high-rise buildings where wind action can be a dominating factor from a structural engineering point of view. Hong Kong was taken as a site for case study in view of the occurrence of high-intensity seasonal typhoons. The systems were hypothesised to adopt a modular system based on an existing 31-storey reinforced-concrete student residence. Three-dimensional finite-element models were developed to investigate the structural behaviours under gravity, wind and seismic actions. The serviceability drift performance, ultimate member strength demand, connection details, overall stability and robustness were compared. The hypothesised building was pushed to a limit of 40 storeys to investigate the structural performance further. The results suggest that the engineered modular structural system is effective to withstand the strong wind and moderate seismic actions demand in Hong Kong, providing a good foundation for exploring innovative structural solutions for high-rise building modularisation.